Conhecimento nas organizações: uma investigação de seus fundamentos - Pacheco, João Alves (2006)
The objective of the study in hand was to perform an analysis, regarding the Genetic Epistemology perspective of Jean Piaget, of some processes present in companies in the service organizations market. In this way, the work in hand assumes as an initial assumption the definition of knowledge from this perspective, also known as constructivism. Considering the premise adopted, it became evident that it s development was inexorably linked to the understanding of reality through a vision that contains a dialetic form in the knowledge concept proposed by the genetic epistemology. In this, the complex vision was ideal approach to deal with the facilitation of a conception of the organization in line with the definition knowledge of genetic epistemology. In addition to this, the ideas present in both perspetives, demonstrate a distinct convergence, contributing to the enriching of the present study. The complex thinking also allowed distinguish the organization identity as for other phenomenon that should be considered in the examination of knowledge in organization. The empirical study was conducted by way of a multiply case study in service companies. The common aspect in these organization is the fact that all of them possess the same brazilian company as a partner. However, it s important to emphasize that these companies operate in distincts segments facilitating diversity in the processes analysed. The library research was fundamental for the understanding of the principles that orientate empirical study. This study allowed the verification of wide range of processes involved in the creation and transmission of knowledge in an organizations, more important than the contents, is the form in wich the contents are presented. In this way, the indentification, characterization and analysis of the processes at the creation of knowledge in these companies from a complex ant constructivist point of view, can contribute to the adoption of more efective and successful strategies of implementation and maintenance of the constructivist processes as an important competitive factor